Tingkat Kemiskinan Provinsi Jawa Tengah Dan Faktor-Faktor Yang Mempengaruhinya, Analisis Empiris Dengan Pendekatan Panel Data - Ilmi, Miftakhul, Muhammad Arif, Se.M,Ec,Dev (2017)
The study was entitled "Poverty Rate of Central Java Province and Its Affecting Factors, Empirical Analysis With Data Panel Approach". This study aims to analyze and know how big the influence of PDRB, Inflation, HDI, UMR, and Unemployment, to poverty in Central Java in 2011-2015. The analysis tool uses panel data regression. The Data Panel is a mix of cross-sections covering thirty-five districts and cities in Central Java and a time series over five years - 175 observations. The results show that Fixed Effect Method (FEM) is the best data panel regression model. Based on the results of the analysis found that GRDP has a negative and significant effect on poverty. While inflation has a negative and significant effect on poverty. While the HDI has negative and insignificant. While Unemployment has positive and insignificant effect Similarly, UMR has positive and significant effect. To that end the government should expand employment and employment opportunities so as to reduce the poverty rate in Central Java. Keyword: Poverty, GDP, Inflation, HDI, UMR, Unemployment